Identification of HLA haplotypes as genetic markers of glomerulonephritis with refractory nephrotic syndrome - S. I. Kudryashov; L. M. Karzakova (Медицинская иммунология, 2024)
One of the urgent problems of medicine is to clarify the pathogenetic mechanisms of glomerulonephritis (GN) with refractory nephrotic syndrome (NS). In 30% of cases, refractory NS has a genetic nature. The role of human histocompatibility system (HLA) genes in the development of refractory NS has not been sufficiently studied. The purpose of this study was to study the association of two-locus haplotypes of HLA class II gene alleles with GN manifested by refractory NS. The typing of HLA class II genes in 136 patients with NS was performed by polymerase chain reaction (PCR), which included the identification of 13 alleles of the DRB1, 8 – DQA1, and 12 – DQB1 loci. The cohort of the examined patients was divided into two groups: a group of patients with refractory NS and a group of patients with rare relapses, with a lack of refractoriness to the therapy. Persons of Chuvash nationality were selected for the study. In the studied groups of patients, the values of the nonequilibrium coupling of alleles (D) were determined to identify characteristic two-locus haplotypes and their frequency according to the formulas of Piazza A. and coauthors. To assess the association of refractory NS with HLA haplotypes, relative risk values (RR) were calculated using the formula Woolf B. and Haldane J. The statistical significance of the association was assessed using the twosided Fisher exact method for four-field tables (PF). The highest value of RR was found in the haplotype HLA-DRB1*11(05)-DQA1*0301. Its value was 42.1 (PF = 0.005). Another statistically significant value was the RR value of the haplotype HLA-DRB1*15(02)-DQB1*0602-8, equal to 0.2 (PF = 0.004). As a result of the study, the haplotype DRB1*11(05)-DQA1*0301, associated with an increased risk of refractory NS, and the protective haplotype DRB1*15(02)-DQB1*0602-8, reducing the risk of refractory NS were found in the HLA genotype of individuals in the Chuvash population.